2017
DOI: 10.4102/sajbm.v48i4.38
|View full text |Cite
|
Sign up to set email alerts
|

Market reaction to tender and private offers on the JSE

Abstract: Investors can benefit when incorporating the information-signalling effect of share repurchases in their investment strategies. Previous South African studies on open market share repurchases confirmed the globally observed signallingeffect, but found open market share repurchases not to be the outright favoured share repurchase type in this country -as is the case globally. The present study is the first to examine the market reaction to the preferred share repurchase type, namely specific (or tender and priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Subsequently, this may result in share price variation within the scope of the research. For example, research conducted by Wesson, Muller and Ward (2018) has identified that standard errors limit certain conclusions about whether the price changes are temporary or permanent. Although the statistical interpretation method aims to mitigate the effect of external occurrences, some factors might not be accounted for.…”
Section: Limitationsmentioning
confidence: 99%
“…Subsequently, this may result in share price variation within the scope of the research. For example, research conducted by Wesson, Muller and Ward (2018) has identified that standard errors limit certain conclusions about whether the price changes are temporary or permanent. Although the statistical interpretation method aims to mitigate the effect of external occurrences, some factors might not be accounted for.…”
Section: Limitationsmentioning
confidence: 99%
“…The repurchase can be executed by the holding company itself or, in some jurisdictions, by subsidiaries and share trusts controlled by the holding company (Bester et al , 2008; Cassim, 2003). Directors state that they repurchase shares to signal to the market that a company is undervalued (and therefore, the share price of a company usually increases subsequent to a share repurchase announcement) (Bhana, 2007; Manconi et al , 2018; Wesson et al , 2014, 2017). Open-market share repurchases create a demand for the company's shares, which can also drive up the share price due to supply-and-demand forces.…”
Section: Introductionmentioning
confidence: 99%